The Effect of Tourism Facilities and Service Quality on Return Intention through Visitor Satisfaction - Arevin, Ayat Taufik (LifeSciFi, 2024)
This study aims to determine the effect of tourism facilities and service quality on revisit intention through visitor satisfaction in Yogyakarta. Tourism managers in Yogyakarta are faced with the demands of exceeding visitor expectations in order to achieve maximum satisfaction. This research method uses a quantitative approach with Partial Least Square (PLS) analysis to test the relationship between the quality of facilities, services, and visitor satisfaction with revisit intention. Data collection was carried out through questionnaires distributed to 170 respondents who were visitors to tourist attractions in Yogyakarta, using non-probability purposive sampling techniques. The results of the analysis showed a significant influence between tourism facilities and service quality on revisit intention, where visitor satisfaction functions as an intervening variable. The p-value of 0.027 for tourism facilities and 0.014 for service quality indicates a significant positive influence of both variables on revisit intention. This finding is in accordance with previous studies which emphasize that visitor satisfaction plays an important role in strengthening the relationship between facilities and service quality with revisit intention. This study provides valuable insights for tourism managers to design more effective improvement strategies to improve the attractiveness and quality of tourism in Yogyakarta.